Rapid growth of a solitary fibrous tumor of the pleura after slow long-term progression: a case report - Daichi Kakibuchi; Shunta Ishihara; Masanori Shimomura; Satoshi Ikebe; Ryota Dobashi; Kazuki Honda; Masayoshi Inoue (Journal of Cardiothoracic Surgery)
Abstract Background Solitary fibrous tumors (SFTs) of the pleura are usually benign. We present a case of SFT of the pleura which grew rapidly after slow long-term progression. Case presentation A 78-year-old man was referred to our hospital for left-sided back pain and shortness of breath. He was found to have a left mediastinal mass at 15 years of age. He remained asymptomatic for 60 years, and chest computed tomography (CT) during treatment of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis revealed that the mediastinal tumor was 8.0 cm in diameter. The size remained unchanged for 3 years but increased to 15.0 cm over the next 5 years. As the left main pulmonary artery was compressed by the mass, there were concerns regarding the worsening of haemodynamics and exacerbation of symptoms of respiratory distress. A sixth-rib intercostal thoracotomy with a posterolateral incision was performed to remove the large tumor. Perioperative steroid administration (methylprednisolone 125 mg/day) and positive pressure ventilation were administered to prevent re-expansion of the pulmonary oedema. The patient was discharged following an uneventful course. The tumor was pathologically diagnosed as an SFT with no malignant findings. Conclusion SFTs require surgical intervention because of their potential for rapid growth.